S134 A retrospective analysis of respiratory infections and nasopharyngitis rates in trials of anti-IL-17A therapies. (12th November 2019) - Hynes, GM; Pavord, ID; Hinks, TSC
Abstract : Introduction: Type-17 immunity, mediated by the cytokine IL-17A, is important in maintaining epithelial barrier integrity and also in host response to extracellular bacterial and fungal infections. However, dysregulation of this pathway is associated with IL-17A-driven diseases such as psoriasis. There is a significant body of literature linking IL-17A with severe forms of asthma, and at least one anti-IL-17A therapy has been trialled in patients with asthma, while another is in development. Therefore it is important to know the effect on host immunity. Aim: To determine whether infection rates are augmented or decreased in clinical trial participants commencing anti-IL-17A therapy for psoriasis in comparison with those receiving placebo. Methods: We performed a retrospective analysis of rates of respiratory infection, nasopharyngitis, and all infections across eight trials of anti-IL-17A therapies (Secukinumab, Ixekinumab and Bimekizumab) for patients with psoriasis. Brodalumab, a biologic targeting the IL-17 receptor, was not included as this also antagonises IL-17C, a cytokine with a different mechanism of action to IL-17A. We pooled data on infection rates, where reported, for analysis using GraphPad Prism 8. Fungal infections, such as candida, were reported inconsistently and events too few for meaningful statistical analysis. Results: Presented in figure 1. There were statistically significant increases in infection rates for those on anti-IL-17A therapy versus placebo for upper respiratory tract infections, nasopharyngitis and all infections. The relative risks (95% confidence intervals) for anti-IL-17A versus placebo were 1.57 (1.19 to 1.97), 1.52 (1.29 to 1.77) and 1.15 (1.04 to 1.28) and the absolute risk increases were 1.79%, 4.12% and 3.44% respectively. The number needed to harm was 56, 24 and 29 for URTI, nasopharyngitis and all infections respectively. Conclusions: Anti-IL-17A therapy appears to be linked to a small but significant increase in infection rates, which is likely due to the beneficial effects of IL-17A in maintaining mucosal immunity. This may contribute to the negative findings of trials of antagonists of this pathway in patients with asthma to date, and moreover challenges the assumption that elevated IL-17A is a driver of severe asthma rather than a beneficial and protective response to airway epithelial injury.